Is the frequency of adult strabismus surgery increasing? - Astle, Andrew T.; Foulsham, Thomas; Foss, Alexander J.; McGraw, Paul V. (Wiley, 2016)
Purpose In recent years there has been an increase in evidence for the functional and psychosocial benefits of correcting strabismus/heterotropia in adults. This study aimed to establish whether there has been an associated change in the frequency of strabismus surgery performed on adults in England since 2000.